2022
DOI: 10.3390/drones6030064
|View full text |Cite
|
Sign up to set email alerts
|

Impact of UAV Hardware Options on Bridge Inspection Mission Capabilities

Abstract: Uncrewed Aerial Vehicles (UAV) constitute a rapidly evolving technology field that is becoming more accessible and capable of supplementing, expanding, and even replacing some traditionally manual bridge inspections. Given the classification of the bridge inspection types as initial, routine, in-depth, damage, special, and fracture critical members, specific UAV mission requirements can be developed, and their suitability for UAV application examined. Results of a review of 23 applications of UAVs in bridge in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…Automating inspection tasks can save lives while being more productive than manual inspection. According to a recent survey on unmanned aerial vehicle (UAV) use in bridge inspection [5], most drones used for inspection tasks rely on GPS navigation with the biggest limiting factor on inspection efficiency being the drones endurance and mobility. Additionally, the authors note that the most popular drones used for surveying by several US Departments of Transportation are not fully autonomous and require expert human pilots [5].…”
Section: A Why Drone Racing?mentioning
confidence: 99%
See 2 more Smart Citations
“…Automating inspection tasks can save lives while being more productive than manual inspection. According to a recent survey on unmanned aerial vehicle (UAV) use in bridge inspection [5], most drones used for inspection tasks rely on GPS navigation with the biggest limiting factor on inspection efficiency being the drones endurance and mobility. Additionally, the authors note that the most popular drones used for surveying by several US Departments of Transportation are not fully autonomous and require expert human pilots [5].…”
Section: A Why Drone Racing?mentioning
confidence: 99%
“…According to a recent survey on unmanned aerial vehicle (UAV) use in bridge inspection [5], most drones used for inspection tasks rely on GPS navigation with the biggest limiting factor on inspection efficiency being the drones endurance and mobility. Additionally, the authors note that the most popular drones used for surveying by several US Departments of Transportation are not fully autonomous and require expert human pilots [5]. The commercial and safety advantages of highly agile drone systems is clear, however research into autonomous drone racing can also help us gain new understandings on how the visual processing and control by human pilots works, as demonstrated in [6].…”
Section: A Why Drone Racing?mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, infrared acquisition instruments are easy to install, for example infrared cameras can be mounted on UAVs for quick and easy thermal image acquisition. 96,97 Pozzer et al 98 used deep learning to identify delamination, cracks, spalling and patches in conventional images and thermal imaging respectively. Data test results from a dam and two concrete bridge decks showed that MobileNetV2 performs well in identifying multiple types of damage in thermal images, identifying 79.7% of damage.…”
Section: Artificial Intelligence Solutions For Bridge Damage Detectionmentioning
confidence: 99%
“…A typical UAV is made up of a frame, motors, control unit, onboard sensors, communication system, and power supply. Furthermore, many UAVs have a dual tube substructure to allow for the installation of various payloads [7].…”
Section: Introductionmentioning
confidence: 99%